2011
DOI: 10.4103/0970-2113.76295
|View full text |Cite
|
Sign up to set email alerts
|

Increased sensitivity of sputum microscopy with sodium hypochlorite concentration technique: A practical experience at RNTCP center

Abstract: Background:In revised national tuberculosis control program (RNTCP), microscopic examination of sputum for AFB plays an important role in the initial diagnosis of tuberculosis. Bacillary concentration after decontamination and liquefaction by 5% sodium hypochlorite is useful in providing increased sensitivity and safety for handling of specimen.Materials and Methods:In this cross-sectional, prospective study, carried out at NKP Salve Institute of Medical Sciences and RC, Nagpur, patients were included accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…Literature indicates that the pretreatment of sputum using NaOCl can improve the sensitivity of the smear microscopy . In the current study, the sensitivity of the direct AFB smear and NaOCl centrifugation method was found to be 67% and 77%, respectively.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Literature indicates that the pretreatment of sputum using NaOCl can improve the sensitivity of the smear microscopy . In the current study, the sensitivity of the direct AFB smear and NaOCl centrifugation method was found to be 67% and 77%, respectively.…”
Section: Discussionmentioning
confidence: 50%
“…In overburdened countries, it is necessary to reduce the turnaround time (the time required for sputum smear preparation and microscopic examination) for sputum processing (typically <1 h) and this can be achieved by suitable pretreatment methods. Literatures indicate that the pretreatment of sputum with sodium hypochlorite (NaOCl) or phenol ammonium sulphate (PhAS) will decrease the turnaround time and enhance the efficiency of direct microscopy . The current study evaluated the performance of two pretreatment procedures for sputum smear microscopy (NaOCl and PhAS methods) and compared their effectiveness with Lowenstein‐Jensen (LJ) culture.…”
Section: Introductionmentioning
confidence: 99%
“…Although its implication will depend on availability of biosafety cabinet, centrifuge, requires standardization of process. But still we can hope its implication for better management of patients [9] [10].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reducing the recommended number of specimens examined from three to two (particularly to two specimens collected on the same day) could probably benefit TB control programs (117,118). Performance of smear microscopy can be optimized by applying sputum processing with bleach, sodium hypochlorite or by use of overnight sedimentation and fluorescence microscopy (119)(120)(121) (122). In a study from Uganda, microscopic examination of 2 smears prepared from a single sputum specimen was as sensitive as standard two-specimen microscopy and that fluorescence microscopy (FM) using a light-emitting diode (LED) light source was more sensitive than conventional LM.…”
Section: Diagnosis Of Tuberculosismentioning
confidence: 99%